Microscale total genomic DNA was used to explore the complete mitochondrial genomes of two biting midge species of the family Ceratopogonidae (Insecta: Diptera) - Xiaohong Jiang; Yao Xie; Qiongyou Liu (BMC Genomics)
Abstract Background Biting midges (Ceratopogonidae, Diptera) are small insects, with body sizes ranging from 1–5 mm, and the family included 6,276 extant and 303 fossil species in 2022. But only a few mitochondrial genomes of Ceratopogonidae species have been reported, and those from several species have not been amplified. Sequencing of total or mitochondrial genomic DNA requires large amounts insect samples; however, obtaining these samples is very difficult for some insect species. The complete mitochondrial genome sequences of some insect species were cloned by long PCR, but degenerate or multiple pairs of primers were needed; thus, the long PCR method was optimized and improved in this study. The optimized method was named the two-fragment cloning method. In this study, we sequenced and analysed the complete mitochondrial genomes of two biting midge species, Forcipomyia (Lasiohelea) humilavolita (16,885 bp) and Dasyhelea bilineata (16,189 bp), via the two-fragment cloning method following the sequencing of PCR products. Results The two mitochondrial genome fragments of F. humilavolita and D. bilineata were successfully cloned by using the two-fragment cloning method with only single-round PCR and the nested PCR method with two-round PCR, respectively. F. humilavolita and D. bilineata showed highly conserved mitogenomes, with similar gene orders, 37 typical genes and a noncoding A + T-rich region. The nucleotide composition of these genomes was highly biased towards A + T nucleotides (78.15% and 78.25%), and the AT skews (-0.001894 and 0.011999), negative GC skews (-0.535714 and -0.217391), and codon usage were determined. All 22 tRNA genes presented typical cloverleaf secondary structures, except for trnS1-NCU, which lacked the dihydrouridine arm. Phylogenetic analyses of the PCGAA and PCG123RNA datasets revealed that F. humilavolita and D. bilineata were grouped together on the same branch as the other Ceratopogonidae species were F. makanensis, F. pulchrithorax, Culicoides arakawae and C. brevitarsis. Conclusion Different PCG genes were terminated with an incomplete T residue and AT skews in F. humilavolita and D. bilineata. Whether these differences occur between species or genera requires study of the complete mitochondrial genomes of more species of Ceratopogonidae, and the two-fragment cloning method can be used for this. In the key first step, the universal primers for cloning COX1 and 16S rRNA from insects are used, so the two-fragment cloning method may be widely used for insects.